CircNEK6 promotes the progression of pancreatic ductal adenocarcinoma through targeting miR-503/CCND1 axis - Zhiying Shao; Xueting Chen; Hui Qiu; Muchen Xu; Xin Wen; Ziqin Chen; Zhengyang Liu; Xin Ding; Longzhen Zhang (Translational Oncology, 2024)
Purpose: The present study aimed to reveal the function and underlying molecular mechanism of circRNA NIMA related kinase 6 (circNEK6) in promoting the progression of pancreatic ductal adenocarcinoma (PDAC). Methods: The differentially expressed circRNAs in three paired PDAC tissues and adjacent tissues were identified by RNA sequencing. CircNEK6 was screened out to further explore its relationship with the prognosis of PDAC patients. The target microRNAs and mRNAs of circNEK6 were analyzed through online databases and detected by quantitative real-time polymerase chain reaction. Cell counting kit-8 assay, clone formation assay, transwell assay, flow cytometry and western blot were used to explore the function of circNEK6 on the biological behaviors of PDAC cells. The in vivo antitumor effect of circNEK6 silencing on PDAC was investigated by nude mouse xenograft models. Results: 203 differentially expressed circRNAs including circNEK6 were identified between paired PDAC tissues and adjacent tissues, and the expression level of circNEK6 was negatively correlated with the prognosis of PDAC patients. The results of in vitro experiments showed that knockdown of circNEK6 repressed the proliferation, migration and invasion, but induced the apoptosis of PDAC cells. Moreover, circNEK6 silencing inhibited tumor growth and prolonged the survival time of PDAC-bearing mice. Mechanistically, miR-503/cyclin D1 (CCND1) axis was predicted and confirmed as the target of circNEK6. Conclusions: CircNEK6 serves as a competing endogenous RNA of CCND1 by absorbing miR-503, which might be treated as a novel and potential target for PDAC treatment.